Necrotizing Enterocolitis in Preterm Neonates: Prognostic Factors and Outcome: Necrotizing Enterocolitis in Preterm Neonates - Marium, Roohiya; Ehsan, Shaista; Tarar, Saba Haider; Farrukh, Amal; Shahid, Nadia; Ahsan, Mehreen (Pakistan Journal of Health Sciences, 2023)
Necrotizing Enterocolitis (NEC) contributes significantly to a high neonatal death rate in Pakistan and other developing countries. A number of elements related to its development are modifiable and can be addressed. Objectives: To evaluate the frequency of NEC, its associated factors and outcome in preterm babies. Methods: This retrospective, cross-sectional study was conducted at Ziauddin University Hospital, Karachi. Medical records of admitted preterm newborns from 1st December 2020 till 1st December 2022 were reviewed and neonates meeting the modified Bell’s diagnostic criteria ,with NEC stage II and III were included. Data pertaining to antenatal period, delivery and postnatal course of the disease were recorded . Data analysis were done using SPSS version-20 and results expressed as frequencies and percentages. Chi square test was applied with p-value statistical significance set at <0.05. Results: The prevalence of NEC was observed to be 7.1%. Male to female ratio was 1.6:1 with 84.5% of the neonates being low birth weight and culture-proven sepsis present in 44.8%. The mortality rate was 32.7%. Thrombocytopenia, hypotension, formula feeds, a positive blood culture and invasive ventilation were significant risk factors for mortality (p-value 0.01) Conclusions: Necrotizing enterocolitis has a high prevalence and mortality in preemies. Sepsis, formula feeding and a low birth weight adversely affect outcome. Early diagnosis and timely intervention can improve survival